Hemorrhagic Pericarditis in a child with primary varicella infection (chickenpox) - Nandeesh B; Mahadevan Anita; Yasha T; Shankar S (Wolters Kluwer Medknow Publications, 2009)
Chickenpox (Varicella) representing the primary infection by Varicella zoster virus is a common benign and self-limited infectious disease of childhood. Although the disease can be associated with complications, they are generally mild and tend to occur in adults and immunocompromised children. Severe and life-threatening complications are extremely rare, particularly those involving the cardiovascular system. We report a malnourished 5-year-old girl with chicken pox complicated by hemorrhagic pericarditis and deep vein thrombosis leading to fatal pulmonary thromboembolism. Though varicella infection runs a benign self-limiting course, it continues to cause significant morbidity and mortality when associated with complications, particularly in malnourished children. Hence, the importance of vaccination and early recognition of complications is emphasized.